IMPLEMENTASI MODEL SUPERVISI BERBASIS KEIKHLASAN DALAM PENINGKATAN KINERJA GURU PAI DI SMP NEGERI KABUPATEN NAGAN RAYA - Herman Herman; Jamaluddin Idris (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2019)
The sincerity-based supervision model is one of the supervision models in promoting the values of sincerity as the first principle in the workplace, building identity in performing and taking actions, and becoming moral force for PAI supervisors when performing the main tasks and functions. However, the problem that most likely to arise in supervising tasks is the lack of sincerity of PAI supervisor when guiding, developing, and improving the performance of PAI teachers. This study uses a